Diseases of the Pomegranate Tree (Texas Journal of Agriculture and Biological Sciences, 2023)
The fecundity of the pomegranate limits the high effectiveness of insecticides, which give many generations and develop in a hidden form, penetrating into the fetus. This article discusses the pomegranate tree, its characteristics and the classics of the pomegranate tree.